Determinação de pesticidas organoclorados em água de manancial, água potável e solo na região de Bauru (SP) - Rissato, Sandra Regina [UNESP]; Libânio, Marcelo; Giafferis, Giselda Passos; Gerenutti, Marli (Sociedade Brasileira de Química, 2004)
This paper evaluates the presence of organochlorinated pesticides in the water supply system of the city of Bauru, State of São Paulo, Brazil. Soil samples were collected in agricultural areas and water samples at several points of the water source (river) and the distribution net. The results of the analyses of the water from the source were compared with the Brazilian classification system for inland waters (CONAMA/86) and the results of analyses of treated water were compared with Brazilian standards for finished drinking water.
Determination of organochlorated pesticides in the water supply system, drinking water and soil of the region of Bauru (SP)
Keywords: organochlorinated pesticides; water; soil; gas chromatograph